Sociologia Digital: apontamentos teórico-metodológicos para uma analítica das mídias digitais - Felipe Padilha (Universidade do Vale do Rio dos Sinos (UNISINOS), 2018)
The article presents a set of theoretical-methodological propositions formulated in the field of Digital Sociology to deal with digital mediated relations. The text is a stimulus to the debate between researchers of the most varied areas of knowledge production that reflect the advent and consolidation of digital technologies from the point of view of their social modeling. In this way, it is a resumption of the historical, social, and economic issues that mark the relations digitally mediated and that present challenges for contemporary social research. The article is structured in three parts, in which we deal with specific moments of the technologies and the analytical tools developed to think them. Initially, we draw a historical panorama of the rise of digital media, then we present the characteristics of the network connection and the implications of relations and interactions digitally mediated for social research. The article tries to show how, since it came to the market, the Web - or commercial Internet interface - has gained new features that allowed the development of new functionalities that are reflected in the treatment given to the theme. Finally, we deal with the contemporary debates of Digital Sociology, presenting the specificities and the current challenges that are placed in this field of studies.